Early Intervention for Psychosis in Canada: What Is the State of Affairs? - Nolin, Marie (Can J Psychiatry, 2016)
OBJECTIVE: Early intervention services (EIS) for psychosis have been developed in several countries, including Canada. There is some agreement about the program elements considered essential for improving the long-term outcomes for patients in the early phase of psychotic disorders. In the absence of national standards, the current state of EIS for psychosis in Canada needs to be examined in relation to expert recommendations currently available. METHOD: A detailed online benchmark survey was developed and administered to 11 Canadian academic EIS programs covering administrative, clinical, education, and research domains. In addition, an electronic database and Internet search was conducted to find existing guidelines for EIS. Survey results were then compared with the existing expert recommendations. RESULTS: Most of the surveyed programs offer similar services, in line with published expert recommendations (i.e., easy and rapid access, intensive follow-up through case management with emphasis on patient engagement and continuity of care, and a range of integrated evidence-based psychosocial interventions). However, differences are observed among programs in admission and discharge criteria, services for patients at ultra high risk (UHR) for psychosis, patient to clinician ratios, accessibility of services, and existence of specific inpatient units. These seem to diverge from expert recommendations. CONCLUSIONS: Although Canadian programs are following most expert recommendations on clinical components of care, some programs lack administrative and organizational elements considered essential. Continued mentoring and networking of clinicians through organizations such as the Canadian Consortium for Early Intervention in Psychosis (CCEIP), as well as the development of a fidelity scale through further research, could possibly help programs attain and maintain the best standards of early intervention. However, simply making clinical guidelines available to care providers is not sufficient for changing practices; this will need to be accompanied by adequate funding and support from organizations and policy makers.